Evidence of production of keV Sn+ ions in the H2 buffer gas surrounding an Sn-plasma EUV source. (1st March 2023) - Rai, S; Bijlsma, K I; Poirier, L; de Wit, E; Assink, L; Lassise, A; Rabadán, I; Méndez, L; Sheil, J; Versolato, O O; Hoekstra, R
Abstract: Charge-state-resolved kinetic energy spectra of Sn ions ejected from a laser-produced plasma (LPP) of Sn have been measured at different densities of the H2 buffer gas surrounding a micro-droplet LPP. In the absence of H2, energetic keV Sn ions with charge states ranging from 4+ to 8+ are measured. For the H2 densities used in the experiments no appreciable stopping or energy loss of the ions is observed. However, electron capture by Sn ions from H2 results in a rapid shift toward lower charge states. At the highest H2 pressure of 6 × 10 − 4 mbar, only Sn 2+ and Sn + ions are measured. The occurrence of Sn + ions is remarkable due to the endothermic nature of electron capture by Sn 2+ ions from H2 . To explain the production of keV Sn + ions, it is proposed that their generation is due to electron capture by metastable Sn 2 + ∗ ions. The gateway role of metastable Sn 2 + ∗ is underpinned by model simulations using atomic collision cross sections to track the charge states of Sn ions while traversing the H2 buffer gas.